Analisis Return Tenaga Kerja Perempuan Yang Memiliki Balita Di Perdesaan Provinsi Sumatera Barat - Yulina Eliza (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2017)
This research was at,the province of west Sumatra in kabupaten Pasaman and Agam. With samples women’s employement has childrean toddler 0 - 4 months, the sample of the as many as 204 people to technique snowball.The method of analyses used is linear regression multiple.The result showed that education repayment significant to affect return with the rate of return is 11,45 years which in SMTA class 3. The first marriage also significantly affects the return on α = 10%. But variable the main work and other work husband were not significant to affect return. This proves that woment’s employement has children aged 0 - 4 months in province of west sumatra continuously trying to work even if is married and her husband works